(untitled) (Chittagong University Journal of Biological Sciences, 2024)
A study was carried out on the birds of Pochamaria in Shilmaria Union Parishad under Puthia Upazila of Rajshahi District through direct field observations during the winter season from October 2009 to March 2010. A total of 54 species of birds belonging to 9 orders, 26 families and 45 genera were recorded. Among them, 26 (48.15%) species were passerines and 28 (51.85%) non-passerines, and 42 (77.8%) were resident species, 8 (14.8%) locally migratory and 4 (7.4%) winter visitor to Pochamaria. A total of 2,394 trees and 158 bamboo clusters support the roosting habitat. The environmental and human impacts on the roosting colonies and their population ecology and conservation awareness need further study. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):59-64 , 2012.